2017
DOI: 10.5194/hess-21-1093-2017
|View full text |Cite
|
Sign up to set email alerts
|

The internal seiche field in the changing South Aral Sea (2006–2013)

Abstract: Abstract. Internal standing waves (seiches) in the South Aral Sea are studied for the first time. The study, based on numerical simulations and field data, focuses on two different campaigns: the first in autumn 2006, when the stratification was weak and there was a mild prevailing northeasterly wind, and the second in autumn 2013, when the stratification was strong and there was a mild easterly wind. Between these two campaigns, the sea surface level decreased by 3.2 m. The periods of the fundamental modes we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…Accordingly, we hypothesize that under the deep oxycline motions, the contiguous sediments undergo alternating redox conditions, with entailing implications for biogeochemical processes controlling the phosphorus (P) fluxes at the sediment-water interface. In a previous study, a threelayer model of the 288 m deep and meromictic northern Lake Lugano predicted the oscillation of the deep chemocline to be up to 10 times greater than that of the thermocline (Salvadé et al, 1988). Hutter (2011) later invoked a field verification of these computational results.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, we hypothesize that under the deep oxycline motions, the contiguous sediments undergo alternating redox conditions, with entailing implications for biogeochemical processes controlling the phosphorus (P) fluxes at the sediment-water interface. In a previous study, a threelayer model of the 288 m deep and meromictic northern Lake Lugano predicted the oscillation of the deep chemocline to be up to 10 times greater than that of the thermocline (Salvadé et al, 1988). Hutter (2011) later invoked a field verification of these computational results.…”
Section: Introductionmentioning
confidence: 95%
“…These findings motivated us to assess whether similar unsteady fluxes also occur in deep lakes where incomplete seasonal mixing creates a deep oxycline between the mixolimnion and a perennially stagnant and denser monimolimnion. The density gradient that is typically present across these layers has been shown to support higher vertical baroclinicity (Salvadé et al, 1988;Roget et al, 2017), whose amplitude is typically larger than that of the thermocline. Accordingly, we hypothesize that under the deep oxycline motions, the contiguous sediments undergo alternating redox conditions, with entailing implications for biogeochemical processes controlling the phosphorus (P) fluxes at the sediment-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing lake area, specific humidity near the lake surface is decreased, and thus the rate of evaporation is increased. Another distinguishing factor of the East Aral Sea is its increasing salinity, which is above 130 ppm [10]. The salinization of the lake leads to vertical stratification, which is characterized by a rapid change in water temperature and salinity level at a given horizontal or vertical region.…”
Section: Evaporation From the South Aral Seamentioning
confidence: 99%
“…Hydrologic analysis of the Aral Sea and surrounding regions has been an active area of research in the last two decades [7][8][9][10][11]. The present study tries to advance previous studies by quantifying different hydrological parameters of the lake using various remote-sensing datasets that can complement each other.…”
Section: Introductionmentioning
confidence: 97%
“…However, momentum is considerable and equilibrium is overshot, resulting in a rocking motion about nodal points for long periods. Roget et al (2017) identified internal waves in the changing South Aral Sea that has approximately 200 km of extension. Wind events of 3 m/s lasting for 5 days were responsible to excite baroclinic motions.…”
Section: Introductionmentioning
confidence: 99%